The status of Leptopelis barbouri Ahl, 1929 and eleven other nomina of the current tree-frog genus Leptopelis (Arthroleptidae) described from East Africa, with a redescription of Leptopelis grandiceps Ahl, 1929 - Gvoždík, Václav; Tillack, Frank; Menegon, Michele; Loader, Simon P. (Zootaxa, 2014)
An investigation of name-bearing types and other relevant type specimens of twelve nominal Leptopelis taxa described from or distributed in the Eastern Arc Mountains in East Africa was carried out. Our aim was to clarify their status and where necessary revise respective nomina. We suggest several nomenclatural and taxonomic actions: 1) Leptopelis barbouri Ahl, 1929 is transferred to the synonymy of Leptopelis flavomaculatus (Günther, 1864) as a junior subjective synonym; 2) Leptopelis grandiceps Ahl, 1929 is resurrected from the synonymy of Leptopelis uluguruensis Barbour & Loveridge, 1928 as a valid species conforming to the tree frogs which have been known as ‘L. barbouri’ and a lectotype is designated; 3) Leptopelis usambarae Ahl, 1929 is transferred from the synonymy of L. uluguruensis Barbour & Loveridge, 1928 to the synonymy of L. grandiceps Ahl, 1929 as a subjective synonym; 4) a lectotype of Leptopelis amaniensis Ahl, 1929 (synonym of L. uluguruensis), Hylambates johnstoni Boulenger, 1897 (synonym of L. flavomaculatus) and Leptopelis signifer Ahl, 1929 (synonym of L. vermiculatus) is designated to stabilize identity of the nomina; and 5) the type locality of Leptopelis martiensseni Ahl, 1929 and Leptopelis tanganus Ahl, 1929 is corrected.